Lúdica y aprendizaje de Ecuaciones Lineales en Octavo Año de Educación General Básica, Unidad Educativa Velasco Ibarra, periodo 2021-2022 - Yangol Guaman, Carlos Alfredo (2022)
The present research work was carried out to improve the concentration and participation in the learning of linear equations through the use and application of the ludic in the students of the eighth year of basic general education of the Educational Unit “Velasco Ibarra” period 2021-2022. The objective of the research was to use the ludic in the learning of linear equations. The research design is quasi-experimental, which was carried out with two groups of students, thus being the parallel to experimental group and parallel to control group, using the playful method. The data collection was carried out by applying a pre-test and post-test to the two groups, the same one that processed the data through the IBM SPSS computer software. The implementation of play in the subject of mathematics tends to motivate the teacher to create a participatory teaching area, it also encourages the student to be a participant in their learning.